Nilai-Nilai Moderasi Beragama dalam Buku Teks Mata Pelajaran Bahasa Arab (Studi Komparasi Buku Teks Terbitan 2015 Dengan Terbitan 2020) - Khanif, Muhammad (Program Studi Pendidikan Bahasa Arab, 2024)
Internalization of the value of religious moderation in Islamic education in Indonesia, has been strengthened by the existence of the 2020-2024 of RPJMN. This internazition has a program derivative, including the fulfil of educational facilities. One of the educational facilities is the fulfil of subject textbooks that support moderate student output. Textbook of Arabic language subjects, one of the subject textbooks compiled by the Ministry of Religion, as an actuazation of religious moderation values in Islamic Education. Arabic language textbooks in the 2013 curriculum, published in 2015 and 2020. Material reinforcement 2015 in scientific thinking, while the power of the 2020 rhythms and religious moderation. Although, in 2015, internalization of the value of religious moderation already exists, but the need for a comparison study of the two textbooks, the extent to which internalization of religious moderation values in textbooks. This study focused on the comparative analysis of religious moderation values in the textbooks of Arabic subjects in class XI Madrasah Aliyah (Senior High School), specialization in natural sciences/Social Sciences/Language, 2015 and 2020. This study uses a descriptive qualitalive library research method which is further analysis by the content analysis method. The results of the analysis of this study were found, that the values of religious moderation in the textbook of Arabic subjects were distributed in the first few parts, in core competencies; Second, in the titles of chapters; Third, in the pictures in the textbook; Fourth, in the reading text; Fifth, in the problem practice